What is the role of indicators as a governance tool to help cities become more sustainable? - Ribeiro, Tatiana Soares Viana; Cortese, Tatiana Tucunduva Philippi; Kniess, Cláudia Terezinha; Conti, Diego de Melo (Revista de Administração da UFSM, 2019)
Cities need continual improvements as they grow, and the government needs to create the means to meet this demand. To assist in sustainable development for communities, ISO 37120 was created to focus on cities, with indicators for urban services and quality of life. This article seeks to understand if Indicators for Sustainable Cities can help Governance make more assertive decisions and improve the residents’ quality of life.